Effects of slaughter weight on carcass characteristics, meat quality, and metabolomics profiling in the longissimus dorsi muscle of Tianfu finishing pigs - Li, Yuanfeng; Tao, Xuan; Zhao, Pinyao; Zhou, Jianchuan; Ao, Xiang (Frontiers in Veterinary Science, 2024)
In order to investigate the effect of slaughter weight (SW) on carcass characteristics and meat quality, we measured the carcass characteristics, meat quality, and amino acid metabolomics characteristics of longissimus dorsi (LD) muscle from Tianfu finishing (TF) pigs. Raising SW to 125 kg or 150 kg increased average backfat thickness (P < 0.01) and intramuscular fat content (P < 0.01), and decreased shear force (P < 0.01). A total of 231 amino acid metabolome from three amino acid classes identified with metabolomics were analyzed, and 93 differentially expressed metabolites (DEMs) were identified (69 up-regulated DEMs and 24 down-regulated DEMs). The DEMs, including urea, 3-iodo-L-tyrosine, N-glycyl-L-leucine, and N, Ndimethylglycine with amino acid metabolism, were significantly induced (P < 0.01). KEGG pathway analysis showed that these DEMs were significantly enriched (P < 0.01) in 135 metabolism pathways, including pathways related to amino acid metabolism, such as arginine and proline metabolism, glycine, serine and threonine metabolism, alanine, aspartate and glutamate metabolism, tryptophan metabolism, and beta-alanine metabolism. Our research findings provided new insights into the impact of SW on amino acid distribution and theoretical support for genetic breeding of meat quality of TF pigs. However, raising SW to 125 kg, or more, decreased the carcass leanness of live TF pigs and had no benefits to pork quality attributes.